PENGARUH RELIGIUSITAS, PERAN LINGKUNGAN, DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MAHASISWA BERKARIR DI LEMBAGA KEUANGAN SYARIAH - Shavira, Lely; Hidayatullah, Maulana Syarif (Jurnal Ekonomi Sakti, 2024)
This research aims to identify, test, and analyze the factors influencing students' interest in choosing a career in Islamic financial institutions. The approach used in this research is a quantitative method with the distribution of questionnaires through Google Forms to 125 students majoring in Islamic economics at Gunadarma University. The collected data were then analyzed using SPSS version 22. The results of this study indicate that, partially (t), religiosity and environmental role variables do not affect students' interest in pursuing a career in Islamic financial institutions, while the job market consideration variable influences students' interest in pursuing a career in Islamic financial institutions. Simultaneously (F), religiosity, environmental role, and job market consideration jointly significantly affect students' interest in pursuing a career in Islamic financial institutions. The Adjusted R Square value in this study is 0.575, indicating that the influence of independent variables on the dependent variable is 57.5%, while the remaining 42.5% is influenced by other variables not included in this study.